AN APPARAISAL OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN PROMOTING HOSPITALITY AND TOURISM OPERATIONS IN NIGERIA - Daspan Samuel Sallau; Alheri Jibi Zim; Mangut Danjuma Gandu; Pyelshak Yusuf; Abdullahi Ibrahim Bala (Scholar Express Journal, 2022)
The paper focused on the contribution of Information and Communication Technology (ICT) in ensuring effective hospitality and tourism operations in Nigeria. The study was able to use a survey research design method where 115 was used as sample size for the study, which was drawn randomly from 6 states representing the 6 regions in Nigeria such as Katsina, Taraba, Plateau, Enugu, Cross River and Lagos respectively. Some of the key objectives of the study established were: 1) To examine the contribution of Information and Communication Technology (ICT) in ensuring effective hospitality and tourism operations in Nigeria. 2) To identify gaps in the level of usage of ICT in the industry and 3) To suggest some possible measures for improving profitability in the hospitality and tourism industry via the use of ICT. Structured questionnaires were administered to the various states through e-mails and were retrieved and analyzed using SPSS package version 21, based on chi-square statistics in order to find out if a relationship exist between the role ICT plays in the hospitality and tourism industry and the level of effectiveness of job operations that may lead to effective job performance. Results of findings shows that p.value < 0.05 is significant at all levels which is an indication that an increase in the use of ICT in the industry may proportionately leads to increase in the effectiveness of job operations in the industry. The researcher finally recommends that staff should be trained in the use of ICT in the industry, high-speed internet should be provided in the hospitality and tourism organizations, websites should be improved for speedy and effective operations and modern equipment should be installed in place for ensuring effective and efficient services among others.
Keywords: ICTs; Hospitality; Tourism; Effective Industry Operations